Psycoeducation Handling The Impact of Cyberbullying on Adolescents at The Bani Adam - Mirawati Mirawati; Zidney Elma Dewata; Echa Syaputri (JUDIMAS, 2022)
This study aims to provide psychoeducation on handling the impact of cyberbullying which includes definitions, aspects, factors, characteristics, impacts and prevention. Cyberbullying is bullying that is carried out repeatedly on purpose, such as making fun of, or activities that intervene and also demean the bullied target on social media, for example Instagram. This act of cyberbullying has a negative impact on victims of bullying, especially teenagers who are the dominant use of social media. With it, it is hoped that it will equip students with knowledge. According to a 2018 survey in Indonesia, there were 49% of internet users who experienced cyberbullying and only 3.6% reported incidents of cyberbullying. A self-control and ways to prevent cyberbullying behavior are: having ethics when using social media, not talking nonsense and being able to make the right decisions, and being able to choose a good environment so that we don't avoid cyberbullying behavior in adolescents which is a period of development and maturity of attitude